Erosion and runoff rates on an Alfisol in Northeastern Brazil - Campos Filho, Olívio Ribeiro; da Silva, Ivandro de França; de Andrade, Alberício Pereira; Leprun, Jean Claude (Pesquisa Agropecuaria Brasileira, 1991)
Soil and water losses were measured in field plots over four years under natural rainfall on an Alfisol in Pernambuco (Northeastern Brazil). Also, different erosion indexes, as suggested by Wischmeier & Smith (1958), were used to estimate soil losses. Runoff water losses averaged about one-fourth of the annual precipitation, and soil erosion occurred at a rate of 81,4 t/ha/year. Monthly soil losses closely followed the patterns of rainfall distribution. Average annual soil losses, as estimated by multiplying EI30 x nomograph erodibility x topographic factor, were highly correlated with field-measured erosion rates. Nevertheless, discrepant figures were found when this comparison was made separately for each year.